Improving American Indian health care : the western Cherokee experience - Steeler, C. William, 1948-1992 (University of Oklahoma Press, 2001)
"Improving American Indian Health Care shares the Western Cherokee experience so that other tribal governments may adopt or adapt the approaches particularly suitable to their own circumstances."--BOOK JACKET.